Barcelona Design System (1914-2014): Essays on Local History - Anna Calvera (Col·lecció Singularitats, 2018)
The precedents of design in Barcelona date back to the early decades of the twentieth century, when the modern arts (poster making, graphics, perfumery and interior design, among others) were experiencing a period of maturity and Catalan artists were enthusiastic members of the European Avant-garde. All these phenomena are dealt with in Barcelona Design System (1914-2014), together with the establishment of the industry, the appearance of institutions created by designers, and the backing given to a profession that aspired to become a discipline. This book, conceived from the perspective of a dialogue between the local and the global, opens up new historical perspectives and offers a transverse reading of the development of an industry that has been incorporated into the mainstream of economic and cultural movements.